Personal Power and Agency When Dealing with Interactive Voice Response Systems and Alternative Modalities - Jill Walsh (Media and Communication, 2018)
In summer 2015, we conducted an exploratory study of how people in the U.S. use and respond to robot-like systems in order to achieve their needs through mediated customer service interfaces. To understand this process, we carried out three focus groups sessions along with 50 in-depth interviews. Strikingly we found that people perceive (correctly or not) that interactive voice response customer service technology is set up to deter them from pursuing further contact. And yet, for the most part, people were unwilling to simply give up on the goals that motivated their initial contact. Consequently, they had to innovate ways to communicate with the automated systems that essentially serve as gatekeepers to their desired ends. These results have implications for communication theory and system design, especially since these systems will be increasingly presented to consumers as social media affordances evolve.